A fast and automatic hole-filling method based on feature line recovery. Issue 6 (19th September 2017) - Xia, Chunhong; Zhang, Hui
ABSTRACT: In this paper, an automatic method to fill holes in triangle mesh models is proposed. Different types of holes can be handled by recovering feature lines that pass through them, and then the recovered feature lines are used for splitting complex holes into small and simple ones, which simplifies the hole-filling problem. Two kinds of splits are considered, curve split and corner split. For curve split, Euler spirals are constructed as feature lines. The required end-points and their corresponding tangent vectors can be automatically identified to initialize the curve. For corner split, the corner point contained in the hole is recovered by optimizing a quadric equation, then multiple feature lines can be constructed automatically. An advantage of this method is that it works on the neighborhood of each hole, which makes it possible to handle huge models with high efficiency compared to other state-of-the-art methods. GRAPHICAL ABSTRACT: